Chemical tests for phaeochromocytoma. Issue 4 (July 1964) - Kelleher, J.; Walters, G.; Robinson, R.; Smith, P.
Abstract : Urinary catecholamines, 4-hydroxy-3-methoxymandelic acid (V.M.A.), and metadrenalines have been estimated in 39 cases of proven phaeochromocytoma and in many hypertensive patients without phaeochromocytoma. The variation in excretion of these substances is described and their diagnostic significance discussed. Excretion of free catecholamines and metadrenalines showed a proportionately greater increase than of V.M.A. in patients with a phaeochromocytoma, and estimation of the first two appears to be diagnostically more reliable. Hingerty's method for catecholamines appears to be a satisfactory screening test, provided that 90 μg. is taken as the upper limit of normal, and estimation of metadrenalines is considered to be the best confirmatory test for phaeochromocytoma.